Eksperimen Pendekatan Scientific Terintegrasi Pada Metode Discovery Learning Pada Pembelajaran Matematika Ditinjau Dari Kemandirian Belajar (Pada Siswa kelas X Semester Genap SMK Muhammadiyah 3 Surakarta TahunAjaran 2014/2015) - Sulistyowati, Dwi; , Dra. Sri Sutarni, M.Pd (2015)
The Objectives of the Research are, (1) the Differences result of mathematic learning concerning on the scientific method, its integrating on the discovery learning and conventional method, (2) the Differences result of mathematic learningby observation on the self-determining study, (3) the interaction between learning method and the self-determining study concerning onthe students' result of mathematic learning. The population of this study is grade tenth Vocational High School Muhammadiyah 3 Surakarta in the semester II academic year 2014/2015.The sample in this study consisted of grade tenth TIPTL as the experimental class and class X TKJ as the control class. The sampling technique is by using random sampling method. The data collection Methods is by using the test method, questionnaire method, and methods of documentation. The data analysis techniques is by using two-way analysis of variance test with different cells, previously tested using analysis prerequisite Lilifors method to test for normality and the homogeneity test method for the Bartlet.From the results of the data analysis with a significance level of 5% is obtained: (1) there is differentiation of discovery learning methods and conventional learning on learning outcom s of mathematics with Fa = 5.44, (2) there is variance of the result of studies terminology by self-determining learning mathematic with Fb = 4, 66 and (3) there is no interaction between teaching methods and the self-determining learning mathematic by the students' with Fab = 0.50.